Pertentangan Keluargadalam Novel Terpilih Fatimah Busu: Family Conflicts in Selected Fatimah Busu’s Novels - M. Zubir, Siti Khariah; Ismail, Nor Hasimah (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2014)
Conflict is a situation in which there is no agreement between two parties which at times may result in unending controversies.Conflicts may also cause protracted rifts because each party wants to be at the upper hand of the situation. Conflict is a situation in which a party with different point of view believes that their adversary will act to oppose them, which may result in an action taken by a party which may be harmful to the other party. Conflicts may also connotes disputes and sometimes contention. Even though conflicts are viewed as something negative, but in some situations, they may also bring in desireable results. In this study, analysis was undertaken to investigate family conflicts in four novels by Fatimah Busu. The study has two objectives, that is to identify the issues of conflicts and th analyze the family conflicts using Islamic psychology approach of Al Ghazali.Findings of this study showed that the issue of family conflicts can be used as examples and standards that are useful to readers in their daily life,